GROWTH AND YIELD OF THREE SUPERIOR VARIETIES OF SOYBEAN ON RAINFED LOWLAND IN PASAMAN REGENCY, WEST SUMATERA - Rifda Roswita; Yohana Yohana; Syahrial Abdullah (Jurnal Pembangunan Nagari, 2020)
Soybean is one of some important food crops in Indonesia. A research with the objective of to evaluate the growth, yield components, and yield of three soybean superior varieties on rainfed lowland has been conducted in Padang Gelugur district, Pasaman Regency, West Sumatra province from April to September 2018. A randomized block design with three treatments and eight replications was used. The treatments were three superior varieties of soybean, namely Anjasmoro, Burangrang, and Devon-1. All varieties were planted at the same plant spacing (40 cm x 10 cm). Other technological components used based on the integrated crops management approach. Results showed that Anjasmoro and Burangrang varieties performed a good growth, produced high yield components, and gave high yield on the rainfed lowland in Pasaman regency, West Sumatra province. Both varieties yielded dry seed weight 3.01 ton per hectare, higher than its yield potentials. Devon-1 variety only produced dry seed weight 2.29 ton per hectare, but it was still significantly hihger than the average yield of soybean in Indonesia and of course in West Sumatra province. Based on the results of thir research, we recommended that Anjasmoro and Burangrang superior varieties of soybean had better be used in the soybean development program on rainfed lowland in Pasaman regency and other locations which have the same characteristics